MART-1 TCR gene-modified peripheral blood T cells for the treatment of metastatic melanoma: a phase I/IIa clinical trial. (September 2022) - Rohaan, M.W.; Gomez-Eerland, R.; van den Berg, J.H.; Geukes Foppen, M.H.; van Zon, M.; Raud, B.; Jedema, I.; Scheij, S.; de Boer, R.; Bakker, N.A.M.; van den Broek, D.; Pronk, L.M.; et al.
Abstract : Background: Adoptive cell therapy with peripheral blood T cells expressing transgenic T-cell receptors (TCRs) is an innovative therapeutic approach for solid malignancies. We investigated the safety and feasibility of adoptive transfer of autologous T cells expressing melanoma antigen recognized by T cells 1 (MART-1)-specific TCR, cultured to have less differentiated phenotypes, in patients with metastatic melanoma. Materials and methods: In this phase I/IIa trial, peripheral blood T cells from HLA-A2∗02:01-positive patients with unresectable stage IIIC/IV melanoma expressing MART-1 were selected and stimulated with anti-CD3/CD28 beads, transduced with a modified MART-1(26-35) -specific 1D3 TCR (1D3HMCys) and expanded in interleukin (IL)-7 and IL-15. Patients received a single infusion of transgenic T cells in a dose-escalating manner. Feasibility, safety and objective response rate were assessed. Results: Twelve pretreated metastatic cutaneous ( n = 7) and uveal ( n = 5) melanoma patients were included. Patient 1 received 4.6 × 10 9 1D3HMCys T cells and experienced grade 5 toxicity after 9 days. Subsequent patients received 5.0 × 10 7 [ n = 3; cohort (c) 2], 2.5 × 10 8 ( n = 2; c3) and 1.0 × 10 8 ( n = 6; c4) 1D3HMCys T cells. The study was prematurely terminated because of dose-dependent toxicity, concerning skin (10/12), eyes (3/12), ears (4/12) and cytokine release syndrome (5/12), with 7 patients experiencing grade 3-5 toxicity. Partial responses were seen in 2/11 (18%) assessable patients and persistence of 1D3HMCys T cells corresponded to infused cell dose. Conclusions: Production of TCR-modified cells as described leads to highly potent T cells. Partial responses were seen in 18% of patients with dose-dependent 'on-target, off-tumor' toxicity and a maximum tolerated dose of 1.0 × 10 8 cells. Highlights: Described culture method leads to highly reactive T cells with a memory stem/central memory phenotype. On-target, off-tumor toxicity was dose-dependent and limited dose escalation. The maximum tolerated cell dose was 1.0 × 10 8 gene-modified T cells. Transfused T cells persisted up to 9 months and was related to cell dose. Optimization of TCR gene therapy should include strategies to limit on-target, off-tumor toxicity.